Knockdown-resistant mutations in head lice (Pediculus humanus capitis) collected from schoolchildren in Riyadh, Saudi Arabia - Imtinan H. Alghashmari; Noha T. Zelai (Scientific Reports)
Abstract Head lice infestation remains one of the most common child problems. This problem is not only attributed to the ability of head lice to spread rapidly but also because of the head lice resistance that develops from incomplete or improper treatment. Pyrethroids are a group of medications that have been widely used for the treatment of head lice. However, in recent years, several countries reported knockdown resistance (kdr). The aim of this study is to evaluate the frequency of pyrethroid-resistant mutations in Riyadh City, Saudi Arabia. To do that, Sanger sequencing was employed to find the frequency of mutated alleles in the voltage-sensitive sodium channel gene (VSSC). The result showed that the frequency of the resistant alleles in T917I was 0.83. In addition, three new mutations (L920F, V966F, and F967L) were detected in the examined samples. These findings highlight the significant prevalence of pyrethroid-resistant mutations, which may be attributed to the cultural and tourism openness that leads to the abundance of numerous job opportunities for different workforces from all around the world.